ADAPTATION PROCESSES OF THE AGRARIAN SECTOR FOR REALIZATION OF THE EXISITING POTENTIAL - Putsenteilo, Petro; Klapkiv, Yuriy; Vovk, Viktoriia (Proceedings of the International Scientific Conference "Economic Sciences for Agribusiness and Rural Economy", 2020)
The agrarian sector of Ukraine with its basic component of agriculture is increasingly becoming the systemformingfactor in the national economy. It creates the factors for maintaining the sovereignty of the state: foodand, within certain limits, the economic and ecological, energy security of the state, ensures the developmentof technologically related branches of the national economy. The main aim of the study was to compare thediversity of agrarian structure and land productivity in Ukraine. The basic commodity positions of agrarianproducts and the existing potential for development are determined. The measures necessary for the developmentof the agrarian sector of Ukraine, the expansion of markets and the successful promotion of agrarianproducts to the world food markets are singled out.